Peran Inspektorat Wilayah Kota dalam Menyelaraskan Komitmen Zona Integritas di Kecamatan dan Kelurahan Kota Bandung - Truna, Laras Pujaswari; R Ginting, Aldo Nathanael; Amin, Fikri Fakhrial; Rahma, Aida Aulia; Sumaryadi, Maritza Hasnadia; Darmawan, Ivan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Inspectorate is one of the institutions responsible for supervising the implementation of regional governments to ensure that they continue to carry out their commitments. The author analyzes the extent of the role of the Bandung City Regional Inspectorate in carrying out this supervision, including to the Regional Apparatus Organizations at the Village and District levels in an effort to build an Integrity Zone. In this case, the author used a qualitative research method with literature studies as a data collection technique. Based on the data obtained, the Bandung City Inspectorate is still less transparent, effective, and accountable in carrying out its duties. This can be indicated by general information that is not accessible, assessments whose parameters are not transparent, and the absence of follow-up to corruption and gratification practices that continue to occur in the public service process. To overcome these conditions, concrete steps such as strengthening supervision, increasing transparency, increasing competence and integrity, and collaborating with external parties are important.